The age of ideology the 19th century philosophers - Aiken, Henry D. (Henry David) 1912-1982 (The Mentor philosophers, 1956)
Basic writings of: Kant; Fichte; Schopenhauer; comte; Mill; Spencer; Marx; Mach; Nietzsche; Kierkegaard; Hegel.